Dampak Emotional Intelligence (EI) Pada Kinerja Karyawan Disektor Perhotelan - Eka Mariyanti; Hengki Afriadi; Puti Embun Sari; Siska Lusia Putri (Universitas Dharma Andalas, 2022)
The purpose of this study is to provide a better understanding of tourism and hospitality management by exploring the competence and application of Emotional intelligence (EI) in the practice of employees/staff at non-star hotels in Mukomuko district, Bengkulu Province. The influence of Competence and Emotional intelligence (EI) on improving business performance is widely recognized in business and management studies. However, it is very limited to research in the context of the tourism and hospitality industry. This research contributes to the literature through a quantitative study on the influence of competence and emotional intelligence (EI) on the performance of hotel employees Dafiz Ananda Mukomuko. Data were collected through a questionnaire with the unit of analysis in this study were hotel employees, totaling 34 respondents. The research findings reveal that competence can make a positive contribution to improving employee performance, for the second hypothesis the results are also significant where Emotional intelligence (EI) influences increasing hotel employee performance. And for the third hypothesis is that Competence and Emotional intelligence (EI) simultaneously affect employee performance improvement which will ultimately affect overall business productivity. Based on the findings of the quantitative investigation, the authors propose a model conceptualizing the role of employee EI in creating a competitive advantage for organizations ABSTRAK Tujuan dari penelitian ini adalah untuk memberikan pemahaman yang lebih baik tentang manajemen pariwisata dan perhotelan melalui eksplorasi kompetensi dan penerapan Emotional intelligence (EI) dalam praktik karyawan/staf pada hotel non bintang di kabupaten Mukomuko Provinsi Bengkulu. Pengaruh Kompetensi dan Emotional intelligence (EI) pada peningkatan kinerja bisnis diakui secara luas dalam studi bisnis dan manajemen. Namun, sangat terbatas pada penelitian dalam konteks industri pariwisata dan perhotelan. Penelitian ini berkontribusi pada literatur melalui studi Kuantitatif tentang Pengaruh Kompetensi dan Emotional intelligence (EI) terhadap kinerja karyawan hotel Dafiz Ananda Mukomuko. Data dikumpulkan melalui Kuesioner dengan unit analisis dalam penelitian ini adalah karyawan hotel yang berjumlah 34 responden. Temuan penelitian mengungkapkan bahwa Kompetensi dapat memberikan kontribusi positif untuk meningkatkan Kinerja Karyawan, untuk hipotesis kedua hasilnya juga signifikan dimana Emotional intelligence (EI) memiliki pengaruh terhadap peningkatan kinerja karyawan hotel. Dan untuk hipotesis ketiga bahwa Kompetensi dan Emotional intelligence (EI) secara simultan berpengaruh terhadap peningkatan kinerja karyawan yang pada akhirnya akan mempengaruhi produktivitas bisnis secara keseluruhan. Berdasarkan temuan dari penyelidikan kuantitatif, penulis mengusulkan model konseptualisasi peran EI karyawan dalam menciptakan keunggulan kompetitif bagi organisasi